Diagnostic Accuracy of Shear Wave Elastography to Differentiate Between Benign and Malignant Thyroid Nodules Taking Histopathology of FNAC Specimen as Gold Standard - Aneeqa Saleem; Latif, Atif; Umaira Qadir; Alina Sayyed; Hussain Rashid Ihsan; Nosheen Sadiq (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine diagnostic accuracy of shear wave elastography to differentiate amongst benign and malignant thyroid nodules taking histopathology of FNAC specimen as gold standard. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital, Multan Pakistan, from Aug 2024 to Jan 2025. Methodology: In this study two hundred and eighty patients underwent ultrasonic shear wave elastography examination for assessment of the thyroid nodules, elasticity index was measured for each patient and a cutoff value of >66Kpa was taken as suspicion for malignancy. All the patients later went through fine needle aspiration biopsy and status of malignancy confirmed by pathologist (taken as gold standard). Results: All the patients successfully underwent the study. The mean age of the patients turned out 48.9±12.97 years whereas male to female ratio was 1.28:1 and average nodule size was 1.04 cm with a range of 0.18 to 2.50 cm. The result Shear wave elastography is 78.18% sensitive, 76.52% specific and 77.68% accurate in distinguishing malignant thyroid nodules with a PPV of 82.69% and NPV of 70.97%. Conclusion: Shear wave elastography is good non-invasive modality in diagnosing the thyroid malignancy with a reasonable percentage of sensitivity and specificity. However, the variable range of its accuracy may advocate more comprehensive studies on the subject.